2004
DOI: 10.1001/jama.292.18.2243
|View full text |Cite
|
Sign up to set email alerts
|

Effect of DHEA on Abdominal Fat and Insulin Action in Elderly Women and Men

Abstract: Context Dehydroepiandrosterone (DHEA) administration has been shown to reduce accumulation of abdominal visceral fat and protect against insulin resistance in laboratory animals, but it is not known whether DHEA decreases abdominal obesity in humans. DHEA is widely available as a dietary supplement without a prescription.Objective To determine whether DHEA replacement therapy decreases abdominal fat and improves insulin action in elderly persons. Design and SettingRandomized, double-blind, placebo-controlled t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
140
3
6

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 236 publications
(176 citation statements)
references
References 46 publications
24
140
3
6
Order By: Relevance
“…Furthermore, in our early research, we found that chickens fed DHEA exhibited decreased body weight and abdominal fat weight with no significant difference in breast and leg muscle weight (Tang et al, 2007). This was in accordance with previous reports that found that DHEA administration reduced abdominal fat accumulation in both rats (Cleary and Zisk, 1986) and elderly women and men (Villareal and Holloszy, 2004). Few studies have reported the effects of DHEA on poultry growth performance or carcass composition.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, in our early research, we found that chickens fed DHEA exhibited decreased body weight and abdominal fat weight with no significant difference in breast and leg muscle weight (Tang et al, 2007). This was in accordance with previous reports that found that DHEA administration reduced abdominal fat accumulation in both rats (Cleary and Zisk, 1986) and elderly women and men (Villareal and Holloszy, 2004). Few studies have reported the effects of DHEA on poultry growth performance or carcass composition.…”
Section: Discussionsupporting
confidence: 92%
“…Administration of DHEA to rats and mice reduces visceral adipose tissue accumulation, and has a protective effect against insulin resistance that occurs with aging. DHEA also has been described to enhance insulin release and protect pancreatic islets from the cytotoxicity effects of interleukin1b and streptozotocin [9][10][11][12][13][14][15][16][17][18][19][20]. However, the mechanisms underlying the effects of DHEA on insulin release and pancreatic islet survival are not completed understood.…”
Section: Introductionmentioning
confidence: 99%
“…There are very consistent reports of significant decreases in HDL cholesterol following DHEA replacement. Two recent studies reported an improvement in some parameters of insulin sensitivity following 12 weeks of DHEA replacement in adrenal insufficiency (50) and six months of DHEA in elderly women (51). The latter study also reported a significant decrease in fat mass as assessed by magnetic resonance imaging (MRI) in 14 women treated for six months (51).…”
Section: Weeksmentioning
confidence: 94%